Assistance in Urban Farming for the Cultivation of Chili Peppers in a Greenhouse Based on Internet of Things Systems - Aisyah; Asnur, Paranita (UPT Publikasi Ilmiah UNISBA, 2025)
Urban farming has become an innovative solution to address landlimitations in urban areas while also enhancing local food security. This article discusses the cultivation of large chili peppers (Capsicum annuum L.) in the Greenhouse of Ulul Ilmi Islamic Boarding School, East Jakarta, which implements Internet of Things (IoT) technology in its Smart Farming system. This program aims to enhance the efficiency and productivity of chili cultivation through guidance and the implementation of advanced technologies, such as automated irrigation systems, greenhouse temperature monitoring, and maintenance practices like fertilization. The assistance results show that the implementation of IoT can improve the efficiency of water, fertilizer, and energy usage, as well as optimize the growth of red chili plants. This technology enables accurate monitoring and more responsive crop management in response to changes in environmental conditions, allowing chili plants to grow healthier and more productively. We expect this development to serve as a model for replication in various other urban locations, thereby supporting sustainable agriculture and enhancing food security in urban environments.